First Report of the Isolation and Molecular Characterization of Rickettsia amblyommii and Rickettsia felis in Central America - Hun Opfer, Ruchilia Laya (2011)
During 2010, 15 adult ticks, identified as Amblyomma cajennense, were collected from horses in Cahuita and Turrialba districts, whereas 7 fleas, identified as Ctenocephalides felis, were collected from a dog in San Jose city, Costa Rica. In the laboratory, three A. cajennense specimens, two from Cahuita and one from Turrialba, were individually processed for rickettsial isolation in cell culture, as was a pool of seven fleas. Rickettsiae were successfully isolated and established in Vero cell culture from the three ticks and from a pool of seven fleas in C6/36 cell culture. The three tick isolates were genotypically identified as Rickettsia amblyommii, and the flea isolate was identified as Rickettsia felis through DNA sequencing of portions of the rickettsial genes gltA, ompA, and ompB of each isolate. In addition, other seven ticks were shown to contain rickettsial DNA. Polymerase chain reaction products of at least two of these ticks were sequenced and also showed to correspond to R. amblyommii. Overall, 66.7% (10/15) of the A. cajennense adult ticks were found to be infected with rickettsiae. This is the first report of a successful isolation in cell culture of R. amblyommii and R. felis from Central America.